2009
DOI: 10.1007/s11033-009-9777-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BTG2 expression on proliferation and invasion of gastric cancer cells in vitro

Abstract: BTG2 (B cell translocation gene 2) is downregulated in several human tumors and has been known as a tumor suppressor in carcinogenesis of thymus, prostate, kidney, and liver. However, little is known about the role BTG2 plays in gastric adenocarcinoma. In the present study, we intended to investigate the influence of BTG2 on the growth, proliferation, apoptosis, invasion and cell cycle of the gastric cancer cell lines SGC7901 and MKN45. BTG2 cDNA was insected into a constitutive vector pcDNA3.1 followed by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…So far, BTG2 has been demonstrated to involve in varied vital cellular functions, such as in cell cycle regulation, in which BTG2 has been found to be able to repress cell cycle progression at G1/S or G2/M phases and function as a pan cell cycle modulator in a cell- or tissue- specific manner9. Thus, BTG2 has been deemed as a tumor suppressor gene in a variety of cancers, including gastric, breast, bladder, and prostate cancer132425262728. Our results indicated that pre-apoptosis dosage of cisplatin (≤40 μM) treatments upregulated BTG2 gene expression determining by immublotting, RT-qPCR, and transient gene expression assays in both LNCaP and PC-3 cells (Figure 2a, 2b, 2c, 2e, 3c, 3d, 3e).…”
Section: Discussionmentioning
confidence: 99%
“…So far, BTG2 has been demonstrated to involve in varied vital cellular functions, such as in cell cycle regulation, in which BTG2 has been found to be able to repress cell cycle progression at G1/S or G2/M phases and function as a pan cell cycle modulator in a cell- or tissue- specific manner9. Thus, BTG2 has been deemed as a tumor suppressor gene in a variety of cancers, including gastric, breast, bladder, and prostate cancer132425262728. Our results indicated that pre-apoptosis dosage of cisplatin (≤40 μM) treatments upregulated BTG2 gene expression determining by immublotting, RT-qPCR, and transient gene expression assays in both LNCaP and PC-3 cells (Figure 2a, 2b, 2c, 2e, 3c, 3d, 3e).…”
Section: Discussionmentioning
confidence: 99%
“…As a tumor suppressor, BTG2 has been found to be down-regulated or absent in a variety of tumors, such as gastric cancer, breast cancer, and melanoma [1921]. Moreover, dysregulation of BTG2 has been shown to contribute to gastric invasion, and metastasis [19].…”
Section: Introductionmentioning
confidence: 99%
“…As a tumor suppressor, BTG2 has been found to be down-regulated or absent in a variety of tumors, such as gastric cancer, breast cancer, and melanoma [1921]. Moreover, dysregulation of BTG2 has been shown to contribute to gastric invasion, and metastasis [19]. Recent studies have demonstrated that BTG2 can be regulated by non-coding RNAs, including miRNAs [22–24], however its association with mature miR-27a in gastric cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because the LH ovulatory surge induces Btg2 expression and Btg2 interacts with Ant2 in preovulatory granulosa cells, the potential role of Btg2 for promoting differentiation of ovarian granulosa cells during ovulation remains to be determined. Btg2 may have important roles in preventing carcinogenesis of the breast (Takahashi et al, 2011), stomach (Zhang et al, 2010), prostate (Ficazzola et al, 2001), kidney (Struckmann et al, 2004), and liver . It would be interesting to test whether the interaction of Btg2 with Ant2 is a common mechanism in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%